Separating Glioma Hyperintensities From White Matter by Diffusion-Weighted Imaging With Spherical Tensor Encoding - Brabec, Jan; Durmo, Faris; Szczepankiewicz, Filip; Brynolfsson, Patrik; Lampinen, Björn; Rydelius, Anna; Knutsson, Linda; Westin, Carl-Fredrik; Sundgren, Pia C.; Nilsson, Markus (Frontiers in Neuroscience, 2022)
Background: Tumor-related hyperintensities in high b-value diffusion-weighted imaging (DWI) are radiologically important in the workup of gliomas. However, white matter may also appear as hyperintense which may conflate interpretation. Purpose: To investigate whether DWI with spherical b-tensor encoding (STE) can be used to suppress white matter and enhance the conspicuity of glioma hyperintensities unrelated to white matter. Materials and methods: 25 patients with a glioma tumor and at least one pathology-related hyperintensity on DWI underwent conventional MRI at 3 T. DWI was performed both with linear and spherical tensor encoding (LTE-DWI and STE-DWI). LTE-DWI here refers to the DWI obtained with conventional diffusion encoding and averaged across diffusion-encoding directions. Retrospectively, the differences in contrast between LTE-DWI and STE-DWI obtained at a b-value of 2000 s/mm2 were evaluated by comparing hyperintensities and contralateral normal-appearing white matter (NAWM) both visually and quantitatively in terms of the signal intensity ratio (SIR) and contrast-to-noise ratio efficiency (CNReff). Results: STE-DWI was more effective than LTE-DWI at suppressing signal from white matter and improved conspicuity of pathology-related hyperintensities. The median SIR improved in all cases and on average by 28 %. The median (interquartile range) SIR was 1.9 (1.6 – 2.1) for STE and 1.4 (1.3 – 1.7) for LTE with a significant difference of 0.4 (0.3 – 0.5) (p < 10-4, paired U-test). In 40 % of the patients, the SIR was above 2.0 for STE-DWI but with LTE-DWI the SIR was below 2.0 for all patients. CNReff of STE-DWI was significantly higher than of LTE-DWI: 2.5 (2.0 – 3.5) vs 2.3 (1.7 – 3.1) with a significant difference of 0.4 (-0.1 – 0.6) (p < 10-3, paired U-test). STE improved CNReff in 70% of the cases. We illustrate the benefits of STE-DWI in three patients where STE-DWI may facilitate an improved radiological description of tumor-related hyperintensity, including one case that could have been missed out if only LTE-DWI was inspected. Conclusions: The contrast mechanism of high b-value STE-DWI results in a stronger suppression of white matter than conventional LTE-DWI and may therefore be more sensitive and specific for assessment of glioma tumors and DWI-hyperintensities.